(untitled) (FEATURES AND PROBLEMS OF IMPLEMENTING ECONOMIC REFORMS IN AZERBAIJAN, 2025)
The article evaluates the concept of sustainable development as an approach that seeks to balance human interests with environmental protection. In other words, this concept - which integrates economic, ecological, and social dimensions - aims to meet both current and future societal needs by creating harmony among economic growth, environmental sustainability, and social equity. Therefore, in today’s world, where environmental degradation is on the rise, the concept of sustainable development has become one of the most widely discussed topics. From this perspective, the article analyzes the essence of the concept of sustainable development, its historical evolution, its theoretical foundations, and various approaches. It also examines the positions of different countries in the 2024 SDG Index, with a particular focus on Azerbaijan’s standing in this area. Keywords: sustainable development, economic growth, environment, natural resources, ecosystems, SDG Index